ANALISIS PENERAPAN PROGRAM INTENTIONALLY STRUCTUREDUNTUK PENINGKATAN LIFE SKILLS MELALUI AKTIVITAS LUAR SEKOLAH (OUT OF SCHOOL ACTIVITIES) DALAM RANGKA POSITIVE YOUTH DEVELOPMENT - Ari Gana Yulianto, - (2022)
ABSTRACT Life skills are one of the components in forming Positive Youth Development. The purpose of this research is to find out intentionally structured programs that are widely used to improve life skills through out-of-school activities, to find out about out-of-school programs used to improve life skills which are included in intentionally structured programs and to find out the results of intentionally structured programs on improving life skills through Out Of School Activities, the research method in this study used Systematic literature review which is a literature review method that identifies, assesses, and interprets all findings on a research topic, to answer predetermined research questions (Kitchenham et al.2007). In this study, researchers used 30 Final Paper journals to review from 210 journals taken from 4 databases, namely Taylor & Francis, Google Scholar, Science Direct, and Sage. The results showed that participation in structured outof-school activity programs was intentional in its application. can produce quality programs where this can contribute to youth development in a positive direction. This shows that the Intentionally structured program that is implemented in outof-school activities in its implementation can influence positive youth development, this can be seen from the increase in the elements the 5C elements in (PYD) namely Competence, Confidence, Connection, Character and Caring Or Compassion. Keywords: Intentionally structured Program, Out Of School Activities, Positive Youth Development ABSTRAK Life skills merupakan salah satu komponen dalam rangka membentuk Positive Youth Development. Tujuan dari penelitian adalah untuk mengetahui Intentionally structured program yang banyak digunakan untuk meningkatkan life skills melalui Out Of School Activities, untuk mengetahui Program luar sekolah yang digunakan dalam peningkatan life skills yang termasuk dalam intentionally structured program Dan untuk mengetahui Hasil intentionally structured program terhadap peningkatan life skills melalui Out Of School Activities, Metode penelitian pada penelitian ini menggunakan Systematic literature review yang merupakan metode literature review yang mengidentifikasi, menilai, dan menginterpretasi seluruh temuan-temuan pada suatu topik penelitian, untuk menjawab pertanyaan penelitian (research question) yang telah ditetapkan sebelumnya (Kitchenham et al. 2007). dalam penelitian ini peneliti menggunakan 30 jurnal Final Paper to bereview dari 210 jurnal yang diambil dari 4 database yaitu Taylor & Francis, Google Scholar, Science Direct, dan Sage, Hasil penelitian menunjukan bahwa partisipasi dalam program aktivitas luar sekolah yang terstruktur di sengaja dalam penerapan nya dapat menghasilkan program yang berkualitas dimana hal ini dapat berkontribusi bagi pengembangan pemuda kearah yang positif hal ini menunjukan bahwa bahwa Program Intentionally structured yang di terapkan dalam aktivitas luar sekolah dalam pelaksanaan nya dapat berpengaruh terhadap pengembangan pemuda positif, hal ini dapat terlihat dari meningkat nya unsur-unsur 5C dalam (PYD) yaitu Competence, Confidence, Connection, Character dan Caring Or Compassion. Kata Kunci: Intentionally structured Program, Aktivitas Luar Sekolah, Pengembangan Pemuda Positif